A Dash of Virtual Milk: Altering Product Color in Virtual Reality Influences Flavor Perception of Cold-Brew Coffee - Wang, Qian Janice; Meyer, Rachel; Waters, Stuart; Zendle, David (Frontiers in Psychology, 2020)
It is well known that the appearance of food, particularly its colour, can influence flavour perception and identification. However, food studies involving the manipulation of product colour face inevitable limitations, from extrinsic flavours introduced by food colouring to the cost in development time and resources in order to produce different product variants. One solution lies in modern Virtual Reality (VR) technology, which has become increasingly accessible, sophisticated, and widespread over the past years. In the present study, we investigated whether making a coffee look milkier in a VR environment can alter its perceived flavour and liking. Thirty-two UK consumers were given four samples of black cold brew coffee at 4% and 8% sucrose concentration. They wore VR headsets throughout the study and viewed the same coffee in a virtual setting. The colour of the beverage was manipulated in VR, such that participants saw either a dark brown or light brown liquid as they sipped the coffee. A full factorial design was used so that each participant tasted each sweetness x colour combination, Participants reported sweetness, creaminess, and liking for each sample. Results revealed that beverage colour as viewed in VR significantly influenced perceived creaminess, with the light brown coffee rated to be creamier than dark brown coffee. However, beverage colour did not influence perceived sweetness or liking. The present study supports the role of VR as a means of conducting food perception studies, either to gain a better understanding of multisensory integration, or, from an industry perspective, to enable rapid product testing when it may be time-intensive or costly to produce the same range of products in the real world. Furthermore, it opens potential future opportunities for virtual reality to promote healthy eating behaviour by manipulating the visual appearance of foods.